Study on the Interaction of the Dopamine Agonist α-Dihydroergocryptine with the Pharmacokinetics of Digoxin - Retzow, Angelika; Althaus, Michael; de Mey, Christian; Mazur, Dago; Vens-Cappell, Bernhard (Arzneimittelforschung, 2000)
Aim: The study was carried out to explore the potential for pharmacokinetic interaction of a single oral dose of α-dihydroergocryptine (CAS 14271-05-7, DHEC, Almirid®) with digoxin. Methods: The serum pharmacokinetics of digoxin were analysed after the administration of single oral doses of 0.5 mg digoxin administered either alone or concomitantly with 20 mg DHEC according to a randomised, non-blinded, two-period cross-over design, with study periods 2 weeks apart. Twelve healthy male subjects, 23 to 39 years of age were enrolled and were investigated in accordance with the protocol. Venous blood was sampled up to 48 h after dosing. Concentrations of digoxin in serum were determined by a competitive radioimmunoassay.Results: The mean Cmax were 1.97 ± 0.87 (after a median tmax of 1 h) and 2.05 ± 0.95 ng/ml (after a median tmax of 0.83 h) after the administration of digoxin with (test) and without (reference) concomitant DHEC, respectively; the corresponding estimated treatment ratio for test: reference was 0.939, 95% CI: 0.781 to 1.129. The mean AUC(0-48) were 13.6 ± 5.0 ng · h/ ml and 13.3 ± 4.7 ng · h/ml for the test and reference treatment, respectively; the corresponding estimated treatment ratio for test: reference was 1.011, 95% CI: 0.866 to 1.142. In addition, no clinically significant changes were observed by ECG monitoring. The tolerability of digoxin alone was good, significantly more adverse events occurred when co-administered with DHEC; these corresponded with the known adverse reaction profile and were of moderte intensity. No premature study termination was thus necessary.Conclusion: The present study did not demonstrate clinically relevant interaction of a single dose of DHEC on the pharmacokinetics of digoxin. On the basis of these observations there is no indication for an a priori adjustment of the dose of digoxin when concomitant treatment with DHEC is initiated.
Keywords: Almirid®; Digoxin; α-Dihydroergocryptine, clinical pharmacokinetics, drug interaction; CAS 14271-05-7; Dopamine agonists